Integrated de novo Analysis of Transcriptional and Metabolic Variations in Salt-Treated Solenostemma argel Desert Plants - Hasan Ahmad (Frontiers Media S.A., 2021)
Solenostemma argel (Delile) Hayne is a desert plant that survives harsh environmental conditions with several vital medicinal properties. Salt stress is a major constraint limiting agricultural production around the globe. However, response mechanisms behind the adaptation of S. argel plants to salt stress are still poorly understood. In the current study, we applied an omics approach to explore how this plant adapts to salt stress by integrating transcriptomic and metabolomic changes in the roots and leaves of S. argel plants under salt stress. De novo assembly of transcriptome produced 57,796 unigenes represented by 165,147 transcripts/isoforms. A total of 730 differentially expressed genes (DEGs) were identified in the roots (396 and 334 were up- and down-regulated, respectively). In the leaves, 927 DEGs were identified (601 and 326 were up- and down-regulated, respectively). Gene ontology and Kyoto Encyclopedia of Genes And Genomes pathway enrichment analyses revealed that several defense-related biological processes, such as response to osmotic and oxidative stress, hormonal signal transduction, mitogen-activated protein kinase signaling, and phenylpropanoid biosynthesis pathways are the potential mechanisms involved in the tolerance of S. argel plants to salt stress. Furthermore, liquid chromatography-tandem mass spectrometry was used to detect the metabolic variations of the leaves and roots of S. argel under control and salt stress. 45 and 56 critical metabolites showed changes in their levels in the stressed roots and leaves, respectively; there were 20 metabolites in common between the roots and leaves. Differentially accumulated metabolites included amino acids, polyamines, hydroxycinnamic acids, monolignols, flavonoids, and saccharides that improve antioxidant ability and osmotic adjustment of S. argel plants under salt stress. The results present insights into potential salt response mechanisms in S. argel desert plants and increase the knowledge in order to generate more tolerant crops to salt stress.